2018
DOI: 10.1073/pnas.1817070115
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically activated ion channel PIEZO1 is required for lymphatic valve formation

Abstract: SignificancePIEZOs are mechanically activated cation channels. Recently, loss-of-function mutations of human PIEZO1 were found among patients with familial lymphedema, suggesting a requirement of PIEZO1 in the lymphatic system. In this paper, utilizing mouse models lacking PIEZO1 in endothelial cells, we show that this ion channel is required for the formation of lymphatic valves, a key structure for proper circulation of lymph in the body. The requirement of PIEZO1 in valve formation provides mechanistic insi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
203
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(217 citation statements)
references
References 47 publications
12
203
1
1
Order By: Relevance
“…Despite these significant advancements, a challenge toward a more complete understanding of the mechanisms of force‐sensing in LECs is that OSS often regulates molecules that also have flow‐independent roles . However, recently the mechanically activated cation channel PIEZO1 was shown to be required for lymphatic valve formation, thereby identifying a putative mechanosensor that may be targeted to help enhance lymphatic valve regeneration.…”
Section: Lymphatic Vessel Physiology Function and Lymphangiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these significant advancements, a challenge toward a more complete understanding of the mechanisms of force‐sensing in LECs is that OSS often regulates molecules that also have flow‐independent roles . However, recently the mechanically activated cation channel PIEZO1 was shown to be required for lymphatic valve formation, thereby identifying a putative mechanosensor that may be targeted to help enhance lymphatic valve regeneration.…”
Section: Lymphatic Vessel Physiology Function and Lymphangiogenesismentioning
confidence: 99%
“…Despite these significant advancements, a challenge toward a more complete understanding of the mechanisms of force-sensing in LECs is that OSS often regulates molecules that also have flowindependent roles. 70 However, recently the mechanically activated cation channel PIEZO1 76 was shown to be required for lymphatic valve formation, 77 thereby identifying a putative mechanosensor that may be targeted to help enhance lymphatic valve regeneration. Although there is a wealth of evidence that fluid forces affect LEC phenotype, to our knowledge, no study has simultaneously examined the interplay of interstitial flow, luminal shear, and cyclic strain in mediating lymphangiogenesis from an intact vessel with facile experimental manipulation.…”
Section: Lymphatic Vessel Mechanobiologymentioning
confidence: 99%
“…A prior report has suggested lack of specificity of Yoda1 for Piezo1 channels 40 but the GsMTx4 toxin used as the basis of this proposal has limited value as a tool for evaluating Piezo1. Other prior studies have shown that genetic deletion of Piezo1 abolishes Yoda1's effects 10,36,41,42 and that Piezo1 knockdown by RNA interference suppresses its effects 14,30,[43][44][45][46] , consistent with Yoda1 having only Piezo1-mediated effects. Specific structure-activity requirements of Yoda1 at Piezo1 have been observed 24 and it does not activate Piezo2 21 .…”
Section: Discussionmentioning
confidence: 52%
“…It will be interesting to see if these functions also rely on the modulation of the expression of ECM proteins by the Piezo-Yap1 axis in angiogenic contexts. Similarly, the downstream targets of piezo are not identified in the lymphatic valves and a number of flow responsive transcription factors such as foxc2 and Nfat1 (Sabine et al, 2012;Sabine et al, 2015;Sweet et al, 2015) are normally expressed of piezo mutants (Nonomura et al, 2018).…”
Section: Yap1 and Hippo Pathways Are Regulators Of The Oft Valve Formmentioning
confidence: 99%